Effects of Kinetin and Gibberellic Acid on Growth and Ion Transport of Rice Under Cadmium Stress - Akter, Sufia; Samad, Rifat (Bangladesh Journal of Botany, 2024)
An experiment was conducted to analyze the effects of kinetin and gibberellic acid on growth, and ion transport of rice (Oryza sativa var. BRRI-80) under cadmium stress. Exogenous application of both kinetin (2 µM) and gibberellic acid (1 µM) alleviated the negative effects of cadmium (Cd) on growth parameters by enhancing the length of both root and shoot, and biomass of Cd stressed rice plants grown on sand culture. Kinetin and GA3 caused decrease in Na+ accumulation while increasing K+ accumulation in both root and shoot. Accumulation of NO3- and PO43- were improved under cadmium stress by kinetin and GA3 in cadmium stressed rice plants. In addition to this, kinetin and GA3 reduced Cd accumulation in the root and shoot of cadmium stressed rice plants. Both kinetin and gibberellic acid were found effective in improving relative water contents in shoots of cadmium stressed rice plants. Bangladesh J. Bot. 53(2): 209-216, 2024 (June)